Prevalence of gestational, placental and congenital malaria in north-west Colombia (2013)
ABSTARCT: The frequency of pregnancy-associated malaria is increasingly being documented in American countries. In Colombia, with higher frequency of Plasmodium vivax over Plasmodium falciparum infection, recent reports confirmed gestational malaria as a serious public health problem. Thick smear examination is the gold standard to diagnose malaria in endemic settings, but in recent years, molecular diagnostic methods have contributed to elucidate the dimension of the problem of gestational malaria. The study was aimed at exploring the prevalence of gestational, placental and congenital malaria in women who delivered at the local hospitals of north-west Colombia, between June 2008 and April 2011. METHODS: A group of 129 parturient women was selected to explore the prevalence of gestational, placental and congenital malaria in a descriptive, prospective and transversal (prevalence) design. Diagnosis was based on the simultaneous application of two independent diagnostic tests: microscopy of thick blood smears and a polymerase chain reaction assay (PCR). RESULTS: The prevalence of gestational malaria (thick smear /PCR) was 9.1%/14.0%; placental malaria was 3.3%/16.5% and congenital malaria was absent. A history of gestational malaria during the current pregnancy was significantly associated with gestational malaria at delivery. Plasmodium vivax caused 65% of cases of gestational malaria, whereas P. falciparum caused most cases of placental malaria. CONCLUSIONS: Gestational and placental malaria are a serious problem in the region, but the risk of congenital malaria is low. A history of malaria during pregnancy may be a practical indicator of infection at delivery.